Passive Balancing Through Intraday Trading: Whether Interactions Between Short-term Trading and Balancing Stabilize Germany’s Electricity System - Koch, Christopher; Maskos, Philipp (International Journal of Energy Economics and Policy, 2020)
Transmission System operators actively balance the electricity system by sending a dispatch signal to suppliers of balancing reserve. When market participants intentionally adapt their intraday positions based on the expected system state, they can also reduce the required dispatch of balancing reserves. This is called passive balancing. The German imbalance price system incites this behavior. This paper examines whether passive balancing prevails in Germany and how it affects the system stability. Our analysis indicates that intraday trading close to gate closure is highly affected by market participants reacting to the latest published system balance. This behavior has a positive impact on system balancing. Intraday trading close to gate closure reduces both the required demand of balancing energy and high system balances up to 5% without causing a critical overshoot of the system. Keywords: Electricity market design; passive balancing; intraday market; electricity portfolio management; strategic behavior JEL Classifications: C32; D47 DOI: https://doi.org/10.32479/ijeep.8750